Lateral Spinal CSF Leaks in Patients with Spontaneous Intracranial Hypotension: Radiologic-Anatomic Study of Different Variants - Schievink, Wouter I.; Maya, Marcel M.; Tay, Angelique Sao-Mai S.; Taché, Rachelle B.; Prasad, Ravi S.; Wadhwa, Vikram; Nuño, Miriam (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: Spinal CSF leaks cause spontaneous intracranial hypotension. Several types of leaks have been identified, and one of these types is the lateral dural tear. Performing myelography with the patient in the decubitus position allows precise characterization of these leaks. The purpose of the current study was to describe the different variants of spontaneous lateral CSF leaks.MATERIALS AND METHODS: This retrospective cohort study included a consecutive group of patients with spontaneous intracranial hypotension and lateral CSF leaks who underwent digital subtraction myelography in the decubitus position and underwent surgery to repair the CSF leak between July 2018 and June 2023.RESULTS: The mean age of the 53 patients (37 women and 16 men) was 35.5 years. Three different variants of lateral CSF leak could be identified. Forty-nine patients (92.5%) had a lateral dural tear associated with the nerve root sleeve. The dural tear was at the axilla of the nerve root sleeve in 36 patients (67.9%) and at the shoulder in 13 patients (24.5%). Four patients (7.5%) had a lateral dural tear at the level of the pedicle that was not associated with the nerve root sleeve. Findings on digital subtraction myelography were concordant with intraoperative findings in all patients. An extradural CSF collection was seen in all patients with a lateral dural tear associated with the nerve root sleeve but in only 2 of the 4 patients with the pedicular variant of a lateral dural tear.CONCLUSIONS: We identified 3 variants of spontaneous lateral dural tears. Most lateral dural tears are associated with extradural CSF collections and arise from either the axilla (67.9%) or the shoulder (24.5%) of the nerve root sleeve. Lateral dural tears at the level of the pedicle (7.5%) not associated with the nerve root sleeve are uncommon and may require specialized imaging for their detection.DSMdigital subtraction myelographySIHspontaneous intracranial hypotension